pengaruh PENGARUH BOOSTER ALAMI TERHADAP PERTUMBUHAN UMBI Amorphophallus paeoniifolius (Dennst.) Nicolson - Ani Sumarningsih; Ariefa Primair Yani; Bhakti Karyadi; Deni Parlindungan; Aprina Defianti (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2025)
[THE EFFECT OF NATURAL BOOSTERS ON THE GROWTH OF TUBERS OF Amorphophallus paeoniifolius (Dennst.) Nicolson.  Amorphophallus paeoniifolius is a plant with high economic value in the food sector due to its glucomannan content of approximately 20%, which plays a role in lowering blood sugar and cholesterol levels. Its tubers are also rich in resistant starch and glucomannan fiber, offering potential for development as a postbiotic. Additionally, this plant is utilized in the food and cosmetic industries and exhibits antibacterial and antifungal properties. However, its cultivation remains limited, primarily due to a lack of information regarding its benefits and propagation techniques. This study aims to analyze the effect of natural growth boosters on the tuber growth of A. paeoniifolius in the conservation area of the Science Education Study Program, Faculty of Teacher Training and Education, University of Bengkulu. The research employed a descriptive method using stem tuber propagation techniques with four treatments: shallot extract, bamboo shoot extract, control (no booster), and Rootone-F, each with six replications. Observed variables included stem height, stem diameter, and the number of shoots over a 10-week period (August–October 2024). The results showed that the shallot treatment yielded the highest growth rate at 66% (4 samples sprouted), followed by Rootone-F at 50% (3 samples), while the control and bamboo shoot treatments each resulted in 16.6% (1 sample). Shallot extract also demonstrated superior efficacy in stimulating the emergence of multiple shoots per tuber. The environmental conditions during the study were optimal, with temperatures of 27.8–32.3 °C, humidity levels of 56.5–77%, and soil pH ranging from 6.15 to 6.5. In conclusion, natural growth boosters, particularly shallot extract, positively influence the tuber growth of A. paeoniifoliu